Pituitary macroadenoma: analysis of intercarotid artery distance compared to controls - Cristian Ferrareze Nunes; Gustavo Augusto Porto Sereno Cabral; José Orlando de Mello Junior; Mario Alberto Lapenta; José Alberto Landeiro (Arquivos de Neuro-Psiquiatria)
ABSTRACT Objective To evaluate the intercarotid distance (ICD) of patients with pituitary macroadenoma and compare to heatlhy controls. Method We retrospectively reviewed contrast-enhanced MRI images from twenty consecutive patients diagnosed with non-functioning pituitary macroadenoma, measured the ICD at two different levels (petrous segment – ICD1 and horizontal cavernous segment – ICD2) and compared to twenty paired controls. Results There was no statistically significant difference of the mean ICD1 between the groups and subgroups. For the ICD2 there was statistically significant difference between the case and controls. However, there was no significant difference between the patients with smaller adenomas and the controls. In contrast, the patients with giant adenomas showed statistically significantly higher ICD2 than the controls. Conclusion The ICD at the horizontal segment of the cavernous carotid tends to be wider in patients with giant pituitary adenomas than in healthy individuals or patients with smaller adenomas.